Declaration on the Establishment of the Arctic Council 1996 - Ottawa Declaration. - Arctic Council, - (Arctic Council, 1996)
Declaration on the Establishment of the Arctic Council - Joint Communique of the Governments of the Arctic Countries on the Establishment of the Arctic Council. Ottawa, Canada Sept 19, 1996